الذكاء الاصطناعي في مجال التعليم العالي والبحث العلمي: دور محوري في تعزيز التعلم وتطوير البحث العلمي.: "ARTIFICIAL INTELLIGENCE IN HIGHER EDUCATION AND SCIENTIFIC RESEARCH: A KEY ROLE IN ENHANCING LEARNING AND ADVANCING SCIENTIFIC RESEARCH." (Al-Aasar, 2025)
This study was conducted in three stages. First, we provide an overview of artificial intelligence (AI) and its recent impact on the education system, addressing key ethical considerations and implementation challenges. In the second stage, we explore the potential implications for learning environments through the lens of constructivism, focusing on AI-supported cognitive development. Additionally, we examine how AI tools can be leveraged to optimize educational processes, leading to transformative changes in educational paradigms and improvements in study practices.This study aims to explore the applications of Artificial Intelligence (AI) in enhancing Arabic language skills for learners. It involves the digitization of the language, development of computer programs, and adaptation of these technologies to better support Arabic language learners, ultimately improving both the learning and teaching processes. The study emphasizes the importance of implementing this project, as it can open new possibilities in educational curricula and teaching methodologies. The review also explores how AI is fostering interdisciplinary research by offering modern computational capabilities that facilitate collaboration across various academic fields. In terms of institutional growth, AI-based systems enhance research output optimization, streamline resource allocation processes, and assist in decision-making regarding research priorities. Additionally, the review will address concerns related to data privacy, bias in AI algorithms, and other ethical issues, such as the potential displacement of researchers. Both the potential benefits and limitations of AI in higher education research and development will be thoroughly examined.